Improving student learning one principal at a time - Pollock, Jane E., 1958- (Association for Supervision and Curriculum Development, 2009)
A companion to the ASCD best-seller Improving Student Learning One Teacher at a Time, this breakthrough approach to supervision offers principals a simple, positive way to help teachers make the right adjustments in curriculum, instruction, assessment, and feedback--the four areas of practice that make the most difference in how learners learn.